Sumber Belajar pada Pembelajaran IPS di MI atau SD - Ahda, Halimatul; Khairani, Intan; Yusnaldi, Eka; Harry, Khairunnisa Dwi; Fatimah, Siti; Lestari, Tirti Dara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This journal discusses about learning resources, which are all the things used to compile teaching materials. Learning resources can be interpreted as places or surrounding environments, objects, and people that contain information used as a means to bring about changes in behavior. Learning resources include learning media and teaching aids that provide information to students or determine the success in facilitating students to achieve learning goals, so that teaching and learning activities can be carried out well and effectively. The components of learning resources are used to support how the learning resources used can be applied well and in accordance with the learning process. The benefits of these learning resources are to provide direct and concrete learning experiences to students and to ensure that the learning process runs well so that the learning objectives in school are achieved. Learning resources come from the words "source" and "learning". According to Poerwadarminta, source means "origin" (in various senses), while the word learning means "to strive (practice, and so on) in order to acquire skill".